2012
DOI: 10.1080/01690965.2010.549667
|View full text |Cite
|
Sign up to set email alerts
|

Handshape monitoring: Evaluation of linguistic and perceptual factors in the processing of American Sign Language

Abstract: We investigated the relevance of linguistic and perceptual factors to sign processing by comparing hearing individuals and deaf signers as they performed a handshape monitoring task, a signlanguage analogue to the phoneme-monitoring paradigms used in many spoken-language studies. Each subject saw a series of brief video clips, each of which showed either an ASL sign or a phonologically possible but non-lexical "non-sign," and responded when the viewed action was formed with a particular handshape. Stimuli vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 26 publications
3
31
1
Order By: Relevance
“…Similar to native signers, bimodal bilinguals (and M2L2 learners of sign language) identify location with few errors in perception (Bochner et al 2011;Williams and Newman 2016a). Unlike native signers, bimodal bilinguals and M2L2 learners have higher error rates for handshape but perceive it early in sign recognition, relatively at the same time as location (Morford and Carlson 2011;Grosvald et al 2012;Morford et al 2008;Williams and Newman 2016b). In summary, previous studies have shown that lexical access in sign language occurs at both sublexical and lexical stages of processing, but may differ based on sublexical features (i.e., handshape or location) and on language experience.…”
Section: Introductionmentioning
confidence: 95%
“…Similar to native signers, bimodal bilinguals (and M2L2 learners of sign language) identify location with few errors in perception (Bochner et al 2011;Williams and Newman 2016a). Unlike native signers, bimodal bilinguals and M2L2 learners have higher error rates for handshape but perceive it early in sign recognition, relatively at the same time as location (Morford and Carlson 2011;Grosvald et al 2012;Morford et al 2008;Williams and Newman 2016b). In summary, previous studies have shown that lexical access in sign language occurs at both sublexical and lexical stages of processing, but may differ based on sublexical features (i.e., handshape or location) and on language experience.…”
Section: Introductionmentioning
confidence: 95%
“…This is a phoneme monitoring task (cf. Grosvald et al, 2012) for signers but can be performed as a purely perceptual matching task by nonsigners. Performance in the task was evaluated by calculating an adapted d 0 .…”
Section: Tasks and Experimental Designmentioning
confidence: 99%
“…Despite these similarities, it is not clear to what extent the processing of the specific phonological parameters of sign languages, such as handshape, location, and movement, recruits functionally different neural networks. Investigation of the mechanisms of sign phonology have often focused separately on sign handshape (Andin, Rönnberg, & Rudner, 2014;Andin et al, 2013;Grosvald et al, 2012;Wilson & Emmorey, 1997) and sign location (Colin, Zuinen, Bayard, & Leybaert, 2013;MacSweeney, Waters, et al, 2008). Studies that have compared these two phonological parameters identified differences in comprehension and production psycholinguistically (e.g., Orfanidou, Adam, McQueen, & Morgan, 2009;Carreiras, Gutiérrez-Sigut, Baquero, & Corina, 2008;Dye & Shih, 2006;Emmorey, McCullough, & Brentari, 2003), developmentally (e.g., Morgan, Barrett-Jones, & Stoneham, 2007;Karnopp, 2002;Siedlecki & Bonvillian, 1993), and neuropsychologically (Corina, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a phoneme monitoring task (cf. Grosvald et al, 2012) for signers, but can be performed as a purely perceptual matching task by non-signers. Performance in the task was evaluated by calculating reaction times and d′.…”
Section: Stimulimentioning
confidence: 99%